2017
DOI: 10.1161/strokeaha.116.015779
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the Use of Seizure Medications After Intracerebral Hemorrhage

Abstract: Background and Purpose-We investigated potential disparities in the use of prophylactic seizure medications in patients with intracerebral hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Patients with ICH do not indiscriminately receive levetiracetam, rather, treatment is generally given to patients at elevated risk for seizures due to lobar hematoma location,(3, 24) and a correspondingly higher CAVE Score. Controlling for lobar hematoma in statistical models was not statistically significant and did not change the association of prophylactic levetiracetam with worse cognitive function HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ICH do not indiscriminately receive levetiracetam, rather, treatment is generally given to patients at elevated risk for seizures due to lobar hematoma location,(3, 24) and a correspondingly higher CAVE Score. Controlling for lobar hematoma in statistical models was not statistically significant and did not change the association of prophylactic levetiracetam with worse cognitive function HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…28 An analysis of 3,422 patients from a multicenter prospective cohort found that White patients were twice as likely as Black patients to receive seizure prophylaxis after ICH, but the association was eliminated in a single-center subset controlling for hematoma location. 29…”
Section: Resultsmentioning
confidence: 99%
“…28 An analysis of 3,422 patients from a multicenter prospective cohort found that White patients were twice as likely as Black patients to receive seizure prophylaxis after ICH, but the association was eliminated in a single-center subset controlling for hematoma location. 29 No studies evaluated for disparities in the application of continuous EEG or utilization of antiseizure medications after seizure. Sex disparities in the utilization of antiseizure medications after ICH have not been investigated.…”
Section: Inpatient Care Setting/general Medical Managementmentioning
confidence: 99%
“…2 That said, the individual studies permit differentiation of patients according to bleeding anatomy. 3 It would be a compelling addition to the literature to examine whether there is any effect modification for antiepileptic effect related to bleeding location.…”
Section: In Replymentioning
confidence: 99%
“…To the Editor: Olfactory loss as a symptom of coronavirus disease 2019 (COVID-19) has been receiving increasing attention globally, with a number of international statements including it as a key symptom of the disease. [1][2][3][4] In response, the emergency department (ED) at Sengkang General Hospital, a tertiary care hospital in Singapore, began actively inquiring about acute olfactory loss (hyposmia or anosmia of less than 14 days' duration) from April 23, 2020, for all patients who presented with…”
Section: Acute Olfactory Loss Is Specific For Covid-19 At the Emergency Departmentmentioning
confidence: 99%